2015
DOI: 10.1080/13658816.2015.1084510
|View full text |Cite
|
Sign up to set email alerts
|

A partitioned and asynchronous cellular automata model for urban growth simulation

Abstract: Cellular automata (CA) models are used to analyze and simulate the global phenomenon of urban growth. However, these models are characterized by ignoring spatially heterogeneous transition rules and asynchronous evolving rates, which make it difficult to improve urban growth simulations. In this paper, a partitioned and asynchronous cellular automata (PACA) model was developed by implementing the spatial heterogeneity of both transition rules and evolving rates in urban growth simulations. After dividing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…In the first step, we applied the calibrated LANDSCAPE model [14] to simulated different land use changes in Wuhan between 2010 and 2020 under the two scenarios, by calculating the area of forest land, grassland and wetland, separately, in different scenarios to reflect the impact of strict cropland protection policy on ecological lands loss. Then, the InVEST model was used to calculate the amount of nutrient export from land use under two different scenarios and analyze the main factors for the impacts of policy on ecosystem service of water purification.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, we applied the calibrated LANDSCAPE model [14] to simulated different land use changes in Wuhan between 2010 and 2020 under the two scenarios, by calculating the area of forest land, grassland and wetland, separately, in different scenarios to reflect the impact of strict cropland protection policy on ecological lands loss. Then, the InVEST model was used to calculate the amount of nutrient export from land use under two different scenarios and analyze the main factors for the impacts of policy on ecosystem service of water purification.…”
Section: Introductionmentioning
confidence: 99%
“…Transition interval represents the evolving rate for cells. We calculated the transition intervals by following Ke et al [42].…”
Section: Land Use Simulation In Different Scenariosmentioning
confidence: 99%
“…These rules are typically extracted from historical growth observed for the urban area under study or for other similar urban areas. Examples of case studies that illustrate the application of CA‐based UGPM can be found in Chaudhuri and Clarke (), Clarke and Gaydos, (), Ke, Qi, and Zeng (), and Van Vliet, White, and Dragicevic (). A widely known CA‐based UGPM is the SLEUTH (slope, land cover, excluded, urban, transportation, and hill‐shade) model (Chaudhuri & Clarke, ).…”
Section: Literature Reviewmentioning
confidence: 99%